1996
DOI: 10.1074/jbc.271.15.9129
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosyl)ation of Histone H1 Correlates with Internucleosomal DNA Fragmentation during Apoptosis

Abstract: The biochemical role of poly(ADP-ribosyl)ation on internucleosomal DNA fragmentation associated with apoptosis was investigated in HL 60 human premyelocytic leukemia cells. It was found that UV light and chemotherapeutic drugs including adriamycin, mitomycin C, and cisplatin increased poly(ADP-ribosyl)ation of nuclear proteins, particularly histone H1. A poly(ADP-ribose) polymerase inhibitor, 3-aminobenzamide, prevented both internucleosomal DNA fragmentation and histone H1 poly(ADP-ribosyl)ation in cells trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 53 publications
2
54
0
1
Order By: Relevance
“…Human promyelocytic leukemic cell line, HL60, was treated with various concentrations of tanshinone IIA for 4 h, and it was found that tanshinone IIA induced internucleosomal DNA fragmentation into the multiples of 180 bp at the concentration of 1 µg/ ml (Figure 2). UV radiation was used as a positive control for the induction of apoptosis (Yoon et al, 1996). In time course experiment in which 3 µg/ml of Tanshinone IIA was treated, 180 bp DNA ladder was generated 2 h after the treatment (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Human promyelocytic leukemic cell line, HL60, was treated with various concentrations of tanshinone IIA for 4 h, and it was found that tanshinone IIA induced internucleosomal DNA fragmentation into the multiples of 180 bp at the concentration of 1 µg/ ml (Figure 2). UV radiation was used as a positive control for the induction of apoptosis (Yoon et al, 1996). In time course experiment in which 3 µg/ml of Tanshinone IIA was treated, 180 bp DNA ladder was generated 2 h after the treatment (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that a biological anti-ERK approach to control neoplastic transformation exploits mechanisms such as PARP cleavage, utilized by common chemotherapeutic agents. 33,34 PARP has been demonstrated to be a useful target for enhancing the cytotoxicity of several drugs. 35 In fact, PARP is cleaved into 89 and 24 kDa fragments that contain the active site and the DNAbinding domain of the enzyme, respectively, during druginduced apoptosis in a variety of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with p53, PARP is a powerful activator of apoptosis. Active PARP can poly-ADP-ribosylate the histone H1 and thereby facilitate DNA fragmentation (Yoon et al, 1996). Inhibition of PARP on the other hand increases cellular susceptibility to alkylating agents by inhibiting DNA repair at the G1 checkpoint (Tentori et al, , 2001.…”
Section: Figurementioning
confidence: 99%